Cytostatic versus cytocidal profiling of quinoline drug combinations via modified fixed-ratio isobologram analysis - Gorka, Alexander P (BioMed Central, 2013)
BACKGROUND: Drug combination therapy is the frontline of malaria treatment. There is an ever-accelerating need for new, efficacious combination therapies active against drug resistant malaria. Proven drugs already in the treatment pipeline, such as the quinolines, are important components of current combination therapy and also present an attractive test bank for rapid development of new concepts. METHODS: The efficacy of several drug combinations versus chloroquine-sensitive and chloroquine-resistant strains was measured using both cytostatic and cytocidal potency assays. CONCLUSIONS: These screens identify quinoline and non-quinoline pairs that exhibit synergy, additivity, or antagonism using the fixed-ratio isobologram method and find tafenoquine – methylene blue combination to be the most synergistic. Also, interestingly, for selected pairs, additivity, synergy, or antagonism defined by quantifying IC(50) (cytostatic potency) does not necessarily predict similar behaviour when potency is defined by LD(50) (cytocidal potency). These data further support an evolving new model for quinoline anti-malarials, wherein haem and haemozoin are the principle target for cytostatic activity, but may not be the only target relevant for cytocidal activity.